Sonata for cello and piano in D major, op. 102, no. 2 (Artaria edition, second issue) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Erdödy, Anna Mária grof, 1780?-1837 (dedicatee)::::::::::::::: (Vienna; Austria; Artaria et Comp., 2023)
First Viennese edition of the Sonata for cello and piano in D major, op. 102, no. 2, second issue, with price indication "Pr 2f C.M." on title page.